Digital Money: Opportunities, Challenges and the Future Outlook - Mulenga, Richard; Matongo, Chimuka; Phiri, Chilizani (International Journal of Finance, 2025)
Purpose: This study explores the opportunities, challenges, and the future outlook of emerging digital currencies in the like of central bank digital currencies (CBDCs), cryptocurrencies, and stablecoins. The aim is to understand how these digital monetary forms are shaping the global digital currency ecosystem. Methodology: A systematic literature review of 281 studies on digital currencies, published between 2010 and 2024, was conducted. The review focused on identifying key themes such as the regulatory landscape for cryptocurrencies, privacy and anonymity concerns, and technological risks associated with digital currencies. Findings: The review unraveled several dominant themes, including increasing efforts by regulatory authorities to develop comprehensive frameworks to provide legal clarity, enhance consumer protection, and foster innovation in the digital finance sector. However, a significant gap was identified in the integration of regulatory frameworks with Behavioral Economic principles. To address this, the study proposes an integrated regulatory-behavioral framework to influence user behaviour and promote the secure and stable adoption of digital currencies. Unique Contribution to Theory, Policy and Practice: The proposed regulatory-behavioral framework offers an innovative approach to digital currency regulation by integrating insights from Behavioral Economics. This contribution highlights the need for collaborative efforts among policymakers to ensure regulations evolve in tandem with advancements in digital financial technologies. The study envisions a future where CBDCs, cryptocurrencies, and stable coins coexist, with CBDCs playing a central role in establishing a stable, accessible, and efficient digital monetary system.